Respuesta :

Answer:

(4 , -6) x = 4.

Step-by-step explanation:

Note that in a pair under ( X , Y) always consists of X as it's 1st element and Y as it's second element.

so now we know that ( ? , -6) has an X value which is unknown.

inorder to find X you'll simply need to use the Y value you're given which is Y = -6 from ( ? , -6)

now plot the y value into the equation

4X + Y = 10 , Y = -6

4X + (-6) = 10

4X + - 6 = 10 ...... we know that A + - B = A - B

4X - 6 = 10

now take -6 to the right side

when -6 is taken to the right side, it changes to +6

and so ..

4X = 10 + 6

4X = 16

now divide both sides by 4 to find X

4X / 4 = 16 / 4

4 the coefficient of X which is 4 cancels with out denominator which is now 4

X = 16 / 4

16 ÷ 4 = 4.